Fostering Inclusive Education through Multilingualism: Towards more Equitable Education? (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
For over 40 years now, the United Nations Educational, Scientific and Cultural Organisation (UNESCO) has been celebrating International Literacy Day by reminding the international community that literacy is a human right and the foundation of all learning. In the year 2017, International Literacy Day was celebrated across the globe under the theme of ‘Literacy in a digital world’. For statistical purposes, UNESCO defines a literate person as someone who can read and write a short simple statement about their life. In recognising its impact on poverty, health, active citizenship, and empowerment, the development community recognises that “illiteracy is a condition that denies people opportunity” (UNESCO, 2018:6). Literacy, besides being a fundamental human right, is a foundation for reaching the overarching goal of reducing human poverty. Institutions today continue to witness an increase in the number of students who are being taught in a language different from their home language. This desktop study is aimed to unpack the trend of language and literacy from the pre- to post-colonial era in sub-Saharan Africa and how this affects learning. The authors reviewed purposively sampled documents relevant to the aim of the study. The article unpacks the trend of language and literacy from the pre- to post-colonial eras and recommends the incorporation of multilingual pedagogies in the present-day classroom and distance education.
Keywords: Distance education; epistemic access; monolingualism; multilingualism; pre-colonial; post-colonial